The cardiovascular response to underwater pedaling at different intensities: a comparison of 4 different water stationary bikes - Giacomini, F.; Ditroilo, M.; Lucertini, F.; de Vito, G.; Gatta, G.; Benelli, P. (The Journal of Sports Medicine and Physical Fitness, 2009)
AIM: Among the fitness activities, cycling in water immersion performed with water stationary bikes (WSB) has become very popular. However, there is a lack of information concerning their physiological demand. The aim of the present study was to assess the cardiovascular responses to four WSBs. METHODS: Twenty-two healthy participants underwent a graded exercise test on a cycle ergometer. Sixteen of them, 8 males (age 31.5±8.2 years) and 8 females (age 31.9±5.8 years) with the same level of peak oxygen consumption (VO2peak) were chosen and submitted, in random order, to four incremental testing sessions performed with four different models of WSB, one with no resistance (WSB1), two with resistance added to the bottom bracket axle (WSB2 and WSB3), one with resistance added to the pedals (WSB4). The VO2peak and heart rate peak (HRpeak) were measured in all five conditions. RESULTS: Since no significant main effect for gender was detected, the data were grouped and analyzed all together. No significant differences were found in VO2peak and HRpeak within the five testing conditions, whilst time to exhaustion (P<0.01) and pedaling frequency (RPM) at volitional exhaustion (P<0.01) were both significantly different across the four WSBs. When pedaling at 70 RPM, the oxygen consumption and heart rate response (as % of VO2peak and HRpeak) were approximately 45% and 60% for WSB1, 60% and 70% for WSB3, 90% and 90% for WSB2 and WSB4, respectively. CONCLUSIONS: The present results provide useful information for instructors and practitioners because they demonstrate that different models of WSBs could elicit very different cardiovascular responses.